The Second Conference of Tamazuj (Intermingling) States North Bahr Al Ghazal State - Final Communique and Reconmmendations (Tufts Archival Research Center, 2005)
The conference is a continuation of the previous Roundtable Conferences held in Merowe and Wau towards reinforcement of the decisions of the first Tamazuj states' conference held in Kadugli in February 2010. The aim of the conference is to assess the performance progress and to get acquainted with decisions, implementation status as well as overcoming impediments.